2022
DOI: 10.1002/adom.202201008
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Lasers on Silicon at Communication Wavelength: A Progress Review

Abstract: including high refractive index contrast with its oxide material, low loss at communication wavelength regime, and significant thermo-optic coefficient for tuning. Contributed by these advantages, various photonic components have been demonstrated on integrated Si photonics platform, including mode couplers, [3][4][5][6] tunable filters, [7][8][9][10] and optical modulators. [11][12][13][14] However, Si itself is an indirect bandgap material, which limits its light emission efficiency. Laser sources on Si rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 245 publications
0
15
0
Order By: Relevance
“…At present, the way to integrate an electric pump light source based on III-V gain materials with an LNOI platform can be roughly divided into hybrid integration, heterogeneous integration, and microtransfer printing, as described below 129 – 134 …”
Section: Electrically Pumped Iii-v Lasers and Amplifiers On Lnoi Plat...mentioning
confidence: 99%
“…At present, the way to integrate an electric pump light source based on III-V gain materials with an LNOI platform can be roughly divided into hybrid integration, heterogeneous integration, and microtransfer printing, as described below 129 – 134 …”
Section: Electrically Pumped Iii-v Lasers and Amplifiers On Lnoi Plat...mentioning
confidence: 99%
“…Excellent reviews of recent advances and future perspectives can be found in [12][13][14][15][16]. In this paper, we further discuss the prospects of on-chip lasers from the perspective of incorporating cutting-edge applications.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) photonics has been intensively investigated due to its excellent compatibility with Si-based complementary metal oxide semiconductor (CMOS) technologies [ 1 , 2 ]. While monolithic Si-compatible solutions for various devices such as detectors, waveguides, and modulators have been available for years, the development of Si photonics has been impeded by the lack of monolithic energy-efficient and cost-effective light sources [ 3 , 4 ]. Owing to a spectroscopically sharp and environment-stable radiative transition at the wavelength (λ) of 1.54 ÎŒm that is highly desired for Si photonics [ 5 ], Er-doped Si is an ideal material for the fabrication of light sources in Si photonics.…”
Section: Introductionmentioning
confidence: 99%